Hindi - Chaudhary , Himanshu; Sharma, Meenu (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
India faces a persistent civic deficit reflected in weak civic sense, low compliance with public norms, and a structural imbalance between rights and duties. Although ancient Indian traditions emphasized collective responsibility, colonial legacies, institutional weaknesses, and growing socioeconomic disparities have eroded civic culture. This study employs qualitative content analysis using historical texts, constitutional provisions, judicial interpretations, comparative international case studies, and interdisciplinary scholarly literature. Thematic coding is used to analyze the socio-legal, political, and educational roots of India’s civic deficit. Findings reveal that India’s civic deficit stems from interconnected structural factors: weak enforcement of laws, lack of experiential civic education, limited trust in institutions, political interference, and socioeconomic inequality. Comparative insights from Japan, Nordic countries, Singapore, and Brazil demonstrate that civic sense improves when experiential education, strong institutional integrity, and participatory governance coexist. Addressing India’s civic deficit requires systemic reforms: reorienting civic education toward experiential learning, strengthening judicial independence, enforcing rules consistently, expanding participatory mechanisms, and promoting community-level ownership. Comparative models show that long-term cultural change requires both structural reforms and citizen-centered engagement.